Peranan Badan Narkotika Nasional Provinsi Daerah Istimewa Yogyakarta Dalam Penegakan Hukum Terhadap Tindak Pidana Narkotika - Fadhlan, Aunu Rofieq, Hartanto, S.H., M.Hum (2017)
This study aims to determine the role and the steps taken by the National Narcotics Agency Special Region of Yogyakarta to control drug trafficking and to know the obstacles faced in carrying out the task. The research method using criptive empirical jurisdiction. The data source consists of the primary data and secondary data, interview the legal data of primary, secondary and tertiary. Data were collected through the study of literature and field research (interviews), then the data is analyzed qualitatively. The study concluded that the National Narcotics Agency Province of Yogyakarta has a role normatively include the investigation include arrest, detention, search, and seizure conducted by the Code of Criminal Procedure (Criminal Procedure Code) and Act No. 35 of 2009 on Narcotics. Steps to be taken by the National Narcotics Agency Province of Yogyakarta to control drug trafficking in the province through prevention, habilitation and eradication of narcotics. Obstacles faced by the ficulty in finding a suspect because the system used perpetrators use cell system is lost, the difficulty of knowing the placement or placement of narcotics, difficulties in rmining the user or the network of narcotics with the seller or the city narcotics because they do not know each other, more sophisticated modus operandi of traffickers in narcotics, and the lack of information from the public about the city while catching narcotics.